Penyuluhan Tentang Pernikahan Dini Pada Remaja Di Desa Benuang Kecamatan Talang Ubi Kabupaten Pali - Mili Aprilia; Raissa Putri Nur Auliyaa; Maya Agustin; Ahmad Dwi Rendika Akbar; Diski Diski; Berliana Ivoni Putri; Nurul Putri Rahmadani; Meta Triyani; Dilla Frisilia Oktriani; Jumana jumana; Melsiana Melsiana; Megawati Megawati; Putri Belka; Ferina Indah Permata; Peni Lia Permata sari; Yola Oktaviani; Novra Vabelta; Sendy Pratiwi Rahmadhani (JURNAL PENGABDIAN KADER BANGSA, 2025)
Underage marriages are still common, especially in rural areas. If a woman marries at too early an age, it will have an impact on the process of pregnancy and childbirth as a result of the immature reproductive state. The form of this community service is in the form of counseling to the target of activities, namely teenagers in Benuang Village, with a total of 30 teenagers about knowledge of underage marriage in adolescents. The instruments used were in the form of pretest and posttest questionnaire leaflets. Evaluation of activities is carried out using a questionnaire on the Impact of underage marriage knowledge pretest posttest. Based on the results obtained, the increase in the number of teenagers with good knowledge from 5 (16,67%) Teenagers increased to 28 (93,33%). It can be concluded that adolescent knowledge increased by 100% before and after counseling. Counseling has been proven to increase adolescent knowledge about the impact of underage marriage.